Exploration Six Ways of Being Religion According to Dale Cannon Based on An Islamic Perspective - Arzaqi, Argha Zidan (Nursyam Center, 2024)
This research aims to provide knowledge development regarding the exploration of religious procedures according to Dale Cannon using an Islamic perspective. The data collecting technique is library research using a qualitative approach. Dale Cannon identified in his book